Correction of Morphofunctional Condition in Students of Special Medical Groups with Ophthalmologic Diseases when Implementing Experimental Control Technology - В. М. Корягін; О. З. Блавт (OVS LLC, 2017)
The objective is to analyze the dynamics of the morphofunctional condition parameters in students with ophthalmologic diseases in special medical groups under the influence of the experimental control technology in physical education of students in these groups.  Materials and methods: the participants in the experiment were 40 students (equal numbers of boys and girls) with ophthalmologic diseases of functional nature. The study used the methods of empirical level: pedagogical experiment, pedagogical testing: methods of registering morphofunctional condition parameters, functional tests, medical and biological tests, methods of mathematical statistics for processing and interpretation of the experimental study results. Results: The study has determined the effectiveness of the experimental control technology in terms of health condition correction in students with ophthalmologic diseases. It has determined the effectiveness of permanent control during physical culture classes as the main means of information support of the management process in physical education of students with ophthalmologic diseases in special medical groups. Conclusions. The systematization and generalization of the whole complex of the final data of the conducted experiment confirm the advantage of the control technology implementation in physical education of students with ophthalmologic diseases in special medical groups.